Prevalence and factors associated with adequate dietary diversity among pregnant women in Nekemte town, Western Ethiopia, 2021 - Bikila, Haile; Ariti, Berhanu Tessisa; Fite, Meseret Belete; Sanbata, Jabessa Hatahu (Frontiers in Nutrition, 2023)
Background Dietary diversity refers to increasing the consumption of a variety of foods. The consumption of diversified food during pregnancy enables the adequate intake of 11 important micronutrients. Inadequate dietary intake during pregnancy is the major determinant factor in the risk of low birth weight infants. It is capable of ensuring the adequate intake of essential nutrients, which can promote good physical health and mental development. Pregnant women require more protein, iron, iodine, vitamin A, folate, and other nutrients. Adequate intake of fruit, vegetables, and animal products throughout the life cycle helps ensure that women enter pregnancy and lactation without deficiencies. Micronutrient deficiency and protein, carbohydrate, and fat intake imbalances are also linked to an increased risk of chronic disease. Objective To assess the prevalence and associated factors with adequate dietary diversity among pregnant woman in Nekemte town, western Ethiopia, 202.1. Methods A community-based cross-sectional study was conducted among 475 pregnant women in the town. We used a systematic random sampling technique. Data were collected through face-to-face interviews by trained data collectors using a validated questionnaire. Before being exported to STATA version 14, data were entered into EpiData version 3.1, cleaned, coded, and checked for missing values. Results from bivariable analysis of p-value less than 0.25 were moved to a multivariable binary logistic regression model for analysis. Finally, multivariable logistic regression with p-value of less than 0.05 was considered statistically significant. Results The Prevalence of adequate dietary diversity was 43.6% (95% CI; 39.1–48.1). Households with the richest wealth index adjusted odds ratio (AOR = 3.17; 95%Confidence Interval = 1.60–6.28), those who have antenatal care (AOR = 2.16; 95%CI = 1.22–3.84), and women who were government employees (AOR = 1.87; 95%CI = 1.01–3.48) were positively associated with adequate dietary diversity. On the other hand, food-insecure households (AOR = 0.34; 95%CI = 0.17–0.66), women who had not changed their meal frequency (AOR = 0.613; 95%CI = 0.38–0.99), and women in their third trimester (AOR = 0.40; 95%CI = 0.20–0.81) were negatively associated with adequate dietary diversity during pregnancy. Conclusion The findings showed that there was a low acceptable level of dietary diversity among pregnant women in the town. Wealth index, antenatal care, women’s occupation, household food insecurity, gestational age, and not changing meal frequency were identified as factors associated with adequate dietary diversity. Therefore, multi-sectoral collaboration is needed to enhance the dietary diversity of pregnant women by promoting women’s employment and strengthening sustainable income-generating activities.